Electric power grid interconnections in Northeast Asia: A quantitative analysis of opportunities and challenges - Otsuki T.; Mohd Isa A.B.; Samuelson R.D. (Elsevier Ltd, 2023)
Cost benefit analysis; Costs; Electric power distribution; Electric power system interconnection; Electric power transmission networks; Fuels; Investments; Linear programming; Renewable energy resources; Electricity trade; Energy systems modeling; Grid interconnections; Northeast Asia; Renewable energies; Electric power system economics; alternative energy; electricity supply; emission control; energy market; linear programing; modeling; renewable resource; Gobi Desert; Northeast Asia; Russian Federation